Analisis Perencanaan Pajak dan Profitabilitas Terhadap Nilai Perusahaan pada Sektor Transportasi dan Logistik Terdaftar di BEI - Mahanani, Setyo; Sidik, Mohamad Hazeem Bin Mohmad; Suryo, Sekar Dian Pramesti; Maghfiroh, Arina Rusda (AKSES: Jurnal Ekonomi dan Bisnis, 2025)
This study was conducted to determine the effect of tax planning and profitability on company value, with a focus on the transportation and logistics sector. Based on the test results, the Random Effect Model (REM) was selected as the most appropriate approach, and a quantitative method with panel data regression analysis was applied. Purposive sampling was used to determine the sample, with the research subjects being transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The research data was unbalanced panel data, covering 58 year-observations. The findings showed that tax planning and profitability had a positive and significant effect on company value.